2010
DOI: 10.1016/j.jconrel.2010.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-enhanced delivery of targeted echogenic liposomes in a novel ex vivo mouse aorta model

Abstract: The goal of this study was to determine whether targeted, Rhodamine-labeled echogenic liposomes (Rh-ELIP) containing nanobubbles could be delivered to the arterial wall, and whether 1 MHz continuous wave ultrasound would enhance this delivery profile. Aortae excised from apolipoprotein-E-deficient (n = 8) and wild-type (n = 8) mice were mounted in a pulsatile flow system through which Rh-ELIP were delivered in a stream of bovine serum albumin. Half the aortae from each group were treated with 1-MHz continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 44 publications
4
66
1
Order By: Relevance
“…However, others have demonstrated that ELIP can be used for localized ultrasound-mediated drug release 43 and delivery. 51 Passive cavitation imaging could be used in these contexts to obtain spatially resolved feedback during a treatment. Optimization of ultrasound insonation pulses based on cavitation emissions has been proposed as an important step in achieving desired bioeffects.…”
Section: Discussionmentioning
confidence: 99%
“…However, others have demonstrated that ELIP can be used for localized ultrasound-mediated drug release 43 and delivery. 51 Passive cavitation imaging could be used in these contexts to obtain spatially resolved feedback during a treatment. Optimization of ultrasound insonation pulses based on cavitation emissions has been proposed as an important step in achieving desired bioeffects.…”
Section: Discussionmentioning
confidence: 99%
“…ultrasound-enhanced delivery of rhodaminelabeled echogenic liposomes (rh-eliP) within the arterial wall to detect atheroma was observed in an ex vivo mouse model. 48 subendothelial penetration of rh-eliP was present in all ultrasound-treated aortae and was absent in those not exposed to ultrasound. almer et al recently investigated a promising new candidate for improved visualization of atherosclerotic plaques.…”
Section: Targeting Of Atherosclerotic Lesions For Tomographic Imagingmentioning
confidence: 87%
“…Ultrasound parameters to enhance the delivery of therapeutic-loaded echogenic immunoliposomes into the arterial wall for the treatment of atherosclerosis were investigated in an ex vivo mouse aorta model. By using anti-ICAM-targeted echogenic liposomes and following the 1-MHz wave ultrasound, greater adherence of the targeted liposomes to vascular endothelium and greater passage across the vessel wall was shown (47). It was also previously observed that targeting liposomes to ICAM-1, VCAM-1, fibrin, fibrinogen, and TF, in addition to application of ultrasound waves, was able to produce the targeted enhancement in the vessel walls 5 min after intravenous administration of targeted liposomes.…”
Section: Liposomesmentioning
confidence: 99%